Age and sex-specific associations of carotid pulsatility with small vessel disease burden in transient ischemic attack and ischemic stroke. Issue 8 (October 2018) - Lau, Kui Kai; Pego, Petra; Mazzucco, Sara; Li, Linxin; Howard, Dominic PJ; Küker, Wilhelm; Rothwell, Peter M
Background: Although large artery stiffness has been implicated in the pathogenesis of cerebral small vessel disease, whether carotid pulsatility, a convenient surrogate marker of arterial stiffness, is similarly associated with global burden of small vessel disease is unknown. Aims: To determine the age and sex-specific associations of carotid pulsatility with global burden of small vessel disease. Methods: We studied consecutive patients with transient ischemic attack or non-disabling ischemic stroke from the Oxford Vascular Study who had a brain MRI and carotid duplex ultrasound during 2002–2014. We determined clinical correlates of common carotid artery (CCA) and internal carotid artery (ICA) pulsatility index (PI) and their associations with the total small vessel disease score on MRI, stratified by age (median = 72). Results: In 587 patients, correlates of CCA and ICA-PI were both independently associated with age, diabetes, and premorbid mean pulse pressure after adjustment for age, sex, and cardiovascular risk factors (all p  < 0.05). ICA-PI was strongly associated with small vessel disease markers and burden, particularly lacunes, in patients aged<70 (age and sex-adjusted odds ratio of top vs. bottom pulsatility index quartile: 5.35, 1.95–14.70, p  = 0.001; increasing small vessel disease score: 2.30, 1.01–5.25, p  = 0.048), but not in patients aged ≥ 70 ( p  > 0.05). No associations between CCA-PI with small vessel disease score were noted at any age. In 94 consecutive patients who also received transcranial Doppler ultrasound, strong associations between middle cerebral artery (MCA)-PI and an increasing small vessel disease score were noted (unadjusted OR–MCA: 4.26, 1.45–12.55, p  = 0.009; ICA: 2.37, 0.81–6.87, p  = 0.11; CCA: 1.33, 0.45–3.96, p =0.61). Conclusions: ICA and MCA-PI are associated with global small vessel disease burden, especially in individuals aged<70 and may be causally related.